KEPEMIMPINAN BERBASIS KESADARAN DALAM MANAJEMEN PENDIDIKAN BUDDHIS: KAJIAN LITERATUR - Ariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational development in the era of globalization and digital disruption is characterized by increasing demands for performance, efficiency, and institutional competitiveness. In practice, however, an excessive focus on technical and administrative aspects often shifts attention away from essential human dimensions, ethical considerations, and the psychological well-being of educational communities. This condition highlights the need for a leadership approach that is not solely outcome-oriented but also capable of addressing educational complexity through reflective and value-based practices. This study aims to examine and formulate a conceptual framework of mindfulness-based leadership within Buddhist educational management by integrating contemporary leadership theories with Buddhist principles of awareness. The study employs a literature review method by analyzing relevant scholarly publications. The findings indicate that mindfulness-based leadership contributes to the enhancement of self-awareness, ethical sensitivity, emotional intelligence, and the quality of leaders’ decision-making processes, while also fostering inclusive and adaptive organizational cultures. These findings suggest that integrating Buddhist awareness into educational leadership practices can serve as both a conceptual and practical foundation for the development of ethical, reflective, and holistic leadership in Buddhist educational institutions